(untitled) (International Journal of Scientific Trends, 2026)
The article examines the category of “subject matter of crime” as one of the key elements of the composition of crime in criminal law. The relevance of the topic is due to the development of information technology, the emergence of digital assets and new forms of ownership, which requires the adaptation of criminal law norms. Based on the analysis of doctrinal approaches, the concept and features of the object of the crime, its relationship and differentiation with the object of encroachment, as well as the difference from the instruments and means of committing a crime are considered. Special attention is paid to the classifications of objects: by physical nature (material and intellectual values), by legal regime (withdrawn from circulation or limited in it) and by cost characteristics as a qualifying feature. The significance of the subject of the crime for the qualification of the act, the delimitation of related structures and the determination of the direction of the encroachment on the example of the norms of the Criminal Code of the Republic of Uzbekistan is revealed.